Determinants of English proficiency among university students: a case study at Universiti Teknologi MARA Kampus Bandaraya Melaka / Amar Soufwan Morazuki and Mohd Noorazwan Mohd Yazid - Morazuki, Amar Soufwan; Mohd Yazid, Mohd Noorazwan (Faculty of Administrative Science and Policy Studies, 2013)
This study examines the determinants of students’ English proficiency of Bachelor Administrative Science of Universiti Teknologi MARA Kampus Bandaraya Melaka. The purpose of the study is to investigate the connection between family background and students’ English proficiency, to determine the relationship of environments and students’ English proficiency, to examine the connection between students’ perceptions towards English language with their English proficiency and to study the relationship of self motivation and students’ English proficiency. Previous studies were used as guidelines to determine what factors to be tested in this study. This study helps the researchers to determine the determinants of students’ English proficiency among universities students in order to improve the students’ level of English. For this study, the researchers used Simple Random Sampling as a method of distributing questionnaires. A questionnaire survey was distributed to 110 respondents among students of Bachelor Administrative Science of Universiti Teknologi MARA Kampus Bandaraya Melaka based on their respective semester. A total of 110 valid responses were obtained. Pilot test, reliability test, normality test, correlation test and demographic test has been used in order to run this study. Based on the study, there is no relationship between the determinants of English proficiency with students’ English proficiency.